A Reform That Includes Eco‐Justice. Issue 2 (8th June 2016) - Gebara, Ivone
Abstract: This article argues that in order to think seriously about an eco‐reformation, we must take the experience of daily life as central to theology. Too often reformations begin with trying to apply traditional theologies and scriptures to contemporary contexts; this is akin to cutting and pasting abstract ideas and scriptures written in other times and cultures onto the present. Instead, the daily, lived experiences of Christians living through periods of climate change should be the basis of the eco‐reformation that is needed. Such a method is able to look at theology and scripture as possible ecological problems in need of new interpretations from within the context of a changing climate.